(untitled) (College of Basic Education Research Journal, 2026)
This research aims to analyze the effectiveness of green education strategies (green project-based learning, community service learning, outdoor learning in nature, and inquiry-based learning) in developing environmental awareness and contributing to the achievement of the Sustainable Development Goals (SDGs) among university learners in the Environmental Education course for the first stage of the Colleges of Basic Education at Wasit University for the academic year 2024-2025. By adopting two research tools: environmental awareness and sustainable development, a sample of (70) male and female students was selected in two groups: one experimental group studied according to green education strategies, and the other a control group studied the Environmental Education course through university lectures. The research is based on a review of recent literature and international reports, and presents a proposed quasi-experimental design to measure the impact. Evidence shows that integrating the "Education for Sustainable Development (ESD) 2030" framework into curricula, coupled with authentic learning experiences in the environment and society, raises environmental knowledge, pro-environmental attitudes and behaviors, and enhances sustainability competencies such as systems thinking and future foresight. The study recommends the inclusion of integrated green modules across subjects, the adoption of intensive awareness and guidance programs, university-community media, and capacity building for teachers in transformative environmental education.